CONCENTRATION OF UREA NITROGEN IN BUFFALO MILK DURING DIFFERENT SEASONS OF THE YEAR IN NORTHEASTERN BRAZIL - Rangel, Adriano Henrique do Nascimento (2013)
This study aimed at assessing the influence of different seasons of the year (dry and rainy) on urea nitrogen (MUN) concentration of buffalo milk in a commercial herd from Rio Grande do Norte state. The region is characterized by a rainy tropical climate with a dry and wet season from August to January and February to July, respectively. Samples were collected monthly from the cooling tank between February 2010 and February 2011, in the morning. Next, they were homogenized and packed in 40-mL plastic flasks, containing the preservative Bronopol® and later sent to the laboratory for urea nitrogen analysis. Although March 2010 exhibited greater ureanitrogen concentration (25.4 ± 4.4 mg/dL) and November the lowest mean (12 ± 0.4 mg/dL), there was no significant variation in milk urea nitrogen in samples collected from cooling tanks during the rainy and dry seasons.